A nonsynonymous gene variant in the adiponutrin gene is associated with nonalcoholic fatty liver disease severity - Sookoian, Silvia Cristina (2009)
We explored the role of the adiponutrin (PNPLA3) nonsynonymous-rs738409 single nucleotide polymorphism (SNP) in genetic susceptibility to nonalcoholic fatty liver disease (NAFLD) and whether this SNP contributes to the severity of histological disease. Two hundred sixty-six individuals were evaluated in a case-control association study, which included 172 patients with features of NAFLD and 94 control subjects. The rs738409 G allele was significantly associated with NAFLD (P < 0.001; OR 2.8 95%, CI 1.5–5.2), independent of age, sex, body mass index (BMI), and Homeostasis Model Assessment (HOMA) index. When we tested the hypothesis of a relation between the SNP and the histological spectrum of NAFLD, a significant association was observed [chi2 19.9, degree of freedom (df): 2, P < 5 × 10−5, adjusted for HOMA and BMI]. The degree of liver steatosis, as evaluated by liver biopsy, was significantly associated with the rs738409 G allele. Patients with CC genotype showed a lower steatosis score (14.9% ± 3.9) in comparison with the CG genotype (26.3% ± 3.5) and GG genotype (33.3% ± 4.0) (P < 0.005). The proportion of the total variation attributed to rs738409 genotypes was 5.3% (β 0.23 ± 0.07; P < 0.002). Our data suggest that the rs738409 G allele is associated not only with fat accumulation in the liver but also with liver injury, possibly triggered by lipotoxicity.